THE EFFECT OF TURNOVER INTENTION ON EMPLOYEE PERFORMANCE AT NAHDLATUL ULAMA HOSPITAL TUBAN - Munir, Miftahul; Sudrajad, Muhammad; Suharsoyo, Didik; Silviana Rahmawati, Eva (jfpublisher, 2022)
Introduction. The problem in this study is the employee turnover rate of at Nahdlatul Ulama Hospital Tuban which is still above the predetermined standard of 5%, while the turnover value in 2021 is an average of 7.44%. Turnover is often used by employees to get or look for better conditions, but this can cause losses for the organization they leave. The purpose of this study was to analyze the effect of Turnover Intention on the performance of honorary employees at at Nahdlatul Ulama Hospital Tuban. Methods. This research was cross sectional design. Sampling technique using proportional random sampling obtained a sample of 71 employees. The analytical technique used was T-test and Kendall Tau correlation to determine the correlation between independent variable (turnover intention) and dependent variable (employee performance). Results & Analysis. The results showed that the value of the Turnover Intention of honorary employees at the Tuban Hospital was included in the medium category and employee performance was also included in the medium category, while the T test showed that the value of sig 0.008 <0.05, which means that there is an effect of Turnover Intention on performance. Honorary employees and Kendal's correlation value of 0.290 have a weak relationship. Discussion. There is an effect of Turnover Intention on the performance of honorary employees at Nahdlatul Ulama Hospital Tuban Tuban, to decrease turnover give rewards to employees who excel, vacation bonuses, and appropriate compensation for employees.